Tehnološko modeliranje energetskih procesov: Zbirka računalniških vaj - Brinovar, Iztok; Igrec, Dalibor (University of Maribor Press, 2022)
Technological Modelling of Power Processes: Collection of Computer Exercises. The collection of computer exercises is intended primarily for first-year students of the master’s study programme at the Faculty of Energy Technology, University of Maribor, as additional teaching material in implementing computer exercises within the course Technological Modelling of Power Processes. It is also directly related in content to the corresponding laboratory exercises. Exercises are designed to experiment with different systems or processes, modelling by using the Matlab/Simulink software package and evaluating mathematical models. In this way, students improve their knowledge and understanding of the mechanisms of operation of the processes and, through practical work, learn about the entire cyclical modelling process. The collection of computer exercises in connection with laboratory exercises and lectures connects the discussed topic into a complete whole.